Natural antioxidants in cancer prevention - Zorica Arsova-Sarafinovska; Aleksandar J. Dimovski (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2013)
It is well known that oxidative stress is an inevitable event in aerobic life. When our cells use oxygen to create energy, a variety of reactive oxygen (ROS) and nitrogen species (RNS) are generated. These species could attack DNA directly and form mutagenic lesions afterwards. According to the oxidative stress hypothesis of aging, the oxidative damage to critical molecules accumulates over the life period and could ultimately impair the body's function. Moreover, severe oxidative stress causes mutations of tumor suppressor genes, known as one of the initial events in carcinogenesis. Furthermore, it could also play a crucial role in the promotion of the multi-step carcinogenesis. On the other hand, the human body possesses a number of mechanisms that counteract oxidative stress by producing antioxidants in situ, or externally supplied them through foods and/or supplements. Indeed, a considerable amount of laboratory evidence from chemical, cell culture, and animal studies indicates that antioxidants may slow down or possibly prevent the cancer development. Yet, the information from recent cohort, case-control and/or ecological studies is less clear. Therefore, the objectives of this review are to compile a compendium of studies, and to identify effective and promising natural antioxidant interventions